Analysis and characterization of ultra thin SOI MOSFET by MEDICI - Shin, Chang Yeop. (2008)
In this work, the charge coupling, breakdown mechanism and self-heating effect were investigated and identified by two-dimensional and two-carrier device simulation. This work provided comprehensive understanding of unique features of ultrathin SOI MOSFETs and contributed to SOI device modeling and design for future high performance, low power/voltage ICs.